2014
DOI: 10.4081/jphia.2014.349
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Tinea capitis infection among primary school children in a rural setting in south-west Nigeria

Abstract: Dermatophyte infection is a common skin disorder. Tinea capitis, infection of the scalp and hair shaft, is the most common dermatophytosis in children aged between six months and pre-pubertal age. The aim of the study was to determine the prevalence, causative agents and to identify predisposing factors among primary school children in a rural community in Sagamu, Ogun state, Nigeria. This was a descriptive cross sectional study. Interviewer administered questionnaire was used. Following a physical examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 25 publications
3
25
3
Order By: Relevance
“…1,13,22,23,25 Similar to other studies, the majority of the tinea capitis cases were among boys below 15 years of age. 22,24,[45][46][47] Mahé et al's 37 study also revealed a lower proportion of tinea capitis (11%), but found higher prevalence rates of pyoderma (37%), contact dermatitis (18%), scabies (13%), and superficial mycosis (13%) compared to our findings.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…1,13,22,23,25 Similar to other studies, the majority of the tinea capitis cases were among boys below 15 years of age. 22,24,[45][46][47] Mahé et al's 37 study also revealed a lower proportion of tinea capitis (11%), but found higher prevalence rates of pyoderma (37%), contact dermatitis (18%), scabies (13%), and superficial mycosis (13%) compared to our findings.…”
supporting
confidence: 67%
“…[19][20][21] Community-based studies in Nigeria have reported prevalence rates of skin diseases (or dermatophytoses alone) between 10% and 64%. 1,13,[22][23][24][25][26][27] The most common skin condition was fungal infections, especially tinea capitis among school-age children, especially boys, accounting for 43% of the skin diseases in the community. 1,13,22,23,25 Other common skin conditions were impetigo, 13,24 scabies, miliaria, pyoderma, 13 and tribal marks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, majority of respondents from lower social economic class had T. capitis. This is in keeping with findings of other studies that revealed the link between lower socio-economic status and prevalence of T. Capitis (Ayanlowo et al, 2014;Akinboro et al, 2011;Ajao et al, 1985). The findings in our study might be due to the fact that parents of children from lower socio economic status may not have enough funds to provide personal clippers, individual combs, bedding materials, and toiletries for their children and this can result in easy spread of infection among such children once one of them is infected from school or in the neighbourhood.…”
Section: Discussionsupporting
confidence: 93%
“…In the tropics, tinea capitis is usually aesthetically unacceptable, as it "can be unsightly or disfiguring" (Fathi and Al-Samarai, 2000). In Nigeria, its prevalence has been correlated with the warm humid climate, crowded living, poor sanitary condition of majority of the populace, which has been enhancing the spread of the disease (Ayanlowo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%